2016
DOI: 10.2337/db15-1517
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Cardiovascular Disease in Type 1 Diabetes

Abstract: Risk factors for cardiovascular disease (CVD) are well-established in type 2 but not type 1 diabetes (T1DM). We assessed risk factors in the long-term (mean 27 years) follow-up of the Diabetes Control and Complications Trial (DCCT) cohort with T1DM. Cox proportional hazards multivariate models assessed the association of traditional and novel risk factors, including HbA1c, with major atherosclerotic cardiovascular events (MACE) (fatal or nonfatal myocardial infarction [MI] or stroke) and any-CVD (MACE plus con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
76
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(80 citation statements)
references
References 47 publications
(43 reference statements)
4
76
0
Order By: Relevance
“…Interestingly, LDL cholesterol was higher in the 30–39-year-olds who developed CVD compared with the noncases, but in the 40–44-year-olds, LDL cholesterol did not differ from noncases. Unfortunately, a full analysis of risk factors is not possible in this report owing to space and the lack of comparable data in the Allegheny County population, but risk factors have been reviewed previously (7) and more recently reported from the DCCT/EDIC study, in which updated weighted-mean HbA 1c was found to be a strong predictor of CVD incidence, second only to age, whereas LDL cholesterol was a significant but weaker predictor (36). These results stress the need for both intensive glycemic control and lipid-lowering therapy, to prevent CVD events.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, LDL cholesterol was higher in the 30–39-year-olds who developed CVD compared with the noncases, but in the 40–44-year-olds, LDL cholesterol did not differ from noncases. Unfortunately, a full analysis of risk factors is not possible in this report owing to space and the lack of comparable data in the Allegheny County population, but risk factors have been reviewed previously (7) and more recently reported from the DCCT/EDIC study, in which updated weighted-mean HbA 1c was found to be a strong predictor of CVD incidence, second only to age, whereas LDL cholesterol was a significant but weaker predictor (36). These results stress the need for both intensive glycemic control and lipid-lowering therapy, to prevent CVD events.…”
Section: Resultsmentioning
confidence: 99%
“…Based on our recent CVD risk factor assessment [5] that identified the most significant risk factors from an extensive panel of previously established and putative risk factors (‘full model’, ESM Table 1), models employed the updated mean values of HbA 1c , SBP, pulse rate, LDLc and the ‘current’ value of log e (triacylglycerols) at the beginning of each 10 year interval as fixed covariates. For example, the 10–20 year models employed the updated mean or current covariate value at year 10, the 11–21 year models used covariate values at year 11, and so on.…”
Section: Methodsmentioning
confidence: 99%
“…This landmark was reached in 2013 and a formal risk factor analysis was carried out. In a multivariable Cox model that also adjusted for age, duration of diabetes, use of angiotensin-converting-enzyme (ACE) inhibitors and a family history of myocardial infarction, the time-weighted updated DCCT/EDIC mean HbA 1c was a stronger predictor of future CVD events than the updated mean systolic BP (SBP), pulse rate, LDL-cholesterol (LDLc), and current triacylglycerols (triacyclglycerol value at time of testing), which also predicted events [5]. …”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, several prospective studies have revealed that hyperglycemia per se, a defining characteristic of diabetes, is an important and independent risk factor for cardiovascular disease in patients with T1D and T2D [46]. Indeed, among individuals with diabetes, a 1 % rise in hemoglobin A1c (HbA1c) levels is associated with a 31 % increase in cardiovascular events [7]. …”
Section: Introductionmentioning
confidence: 99%